The Symbolic Meaning of Costumes and Props in Tari Piriang Suluah Nagari Gunung Padang Panjang Dance - Hasya Hanani Putri; Irfansyah Irfansyah; Novina Yeni Fatrina (Gorga : Jurnal Seni Rupa, 2025)
Tari Piriang Suluah is one of the traditional performing arts of the Nagari Gunung Padang Panjang community. It serves not only as a form of entertainment but also as a reflection of the worldview, customary values, and cultural identity of the Minangkabau people. Although it has become an integral part of local cultural life, the aspects of costume and props in Tari Piriang Suluah have received limited scholarly attention, particularly regarding their symbolic meanings. This study aims to explore the symbolic meanings embedded in the costumes and props of Tari Piriang Suluah as representations of the cultural identity of the Nagari Gunung Padang Panjang community. A descriptive qualitative method with an ethnographic approach was employed. Data were collected through observation, in-depth interviews, documentation, and literature review. The data were then analyzed using Spradley’s domain, taxonomic, and componential analysis techniques, supported by Clifford Geertz’s theory of symbols. The findings reveal that each element of the costume and props in Tari Piriang Suluah embodies symbols that reflect modesty, religiosity, hard work, spiritual values, and the balance of life within the Nagari Gunung Padang Panjang community. These findings affirm that the visual elements in Tari Piriang Suluah function as a medium of cultural communication and a symbolic system that reinforces local identity and values amid the forces of modernization.